Web-Based Collaborative Project-Based Learning in Secondary Education: A Qualitative Study of Students’ Analytical Thinking and Collaboration - Era Octafiona (Jurusan Teknik Informatika dan Komputer, 2025)
Learning in secondary education increasingly requires instructional approaches that are capable of fostering students’ analytical thinking and collaborative skills in response to the demands of 21st-century competencies. However, classroom practices in many schools remain dominated by teacher-centered instruction, which limits students’ opportunities to engage in higher-order thinking and sustained collaboration. As a result, students often experience learning activities that emphasize content reception rather than analytical exploration and cooperative problem-solving.Collaborative learning has been widely adopted as an alternative approach to address these challenges by encouraging students to work together, exchange ideas, and solve problems collectively. Despite its potential, conventional collaborative learning practices frequently encounter practical limitations, such as uneven student participation, time constraints during classroom sessions, and restricted access to diverse learning resources. These limitations reduce the effectiveness of collaboration in supporting deeper analytical engagement among students.Recent developments in educational technology have introduced Web-Based Project-Based Learning (PjBL) as an instructional approach that integrates collaborative project work with digital platforms supporting both synchronous and asynchronous interaction. Through web-based environments, students are able to access learning resources independently, coordinate tasks digitally, and produce authentic learning outputs beyond classroom boundaries. Prior studies have reported that Web-Based PjBL can support higher-order thinking and collaborative skills; however, much of the existing research focuses on general effectiveness or higher education contexts, with limited attention to how web-based collaboration transforms conventional collaborative learning practices at the secondary school level.In the context of Indonesian high schools, empirical evidence regarding the implementation of Web-Based Collaborative PjBL remains limited, particularly studies that explore how this approach strengthens students’ analytical thinking and teamwork through actual classroom practices. Moreover, few studies have examined the transition process from traditional collaborative learning to web-based collaborative projects and the roles of teachers and students during this transformation.Therefore, this study aims to examine the implementation of Web-Based Collaborative Project-Based Learning in a senior high school context, focusing on how this approach strengthens students’ analytical thinking and cooperation. By adopting a qualitative descriptive design, this study seeks to provide an in-depth understanding of learning activities, teacher facilitation, and student collaboration within a web-based project environment, thereby contributing empirical insights into the practical integration of digital collaboration in secondary education.